LEGAL IMPLICATIONS OF MARRIAGE DISPENSATION POST AMENDMENT TO ACT NUMBER 1 OF 1974 CONCERNING MARRIAGE - Komalasari. M, Firlyanti; Nawi, Syahruddin; Zainuddin, Zainuddin (IBLAM LAW REVIEW, 2023)
This study aims to explore what factors are used as urgent reasons in filing a Marriage Dispensation case, including examining the extent to which the Marriage Dispensation case examination process determines the fulfillment of urgent reasons as a requirement for deviations from the minimum age limit for marriage and to find out what are the legal impacts/implications that arise regarding the Dispensation Marriage at the Mamuju Religious Court after the amendment to the Marriage Law. The research method used in this study is empirical legal research, which is carried out using an approach to legal reality in society based on the presence of symptoms in the form of a gap between expectations (das solen) and reality (das sein) in the field of law, where the data collected or collected from the field used to obtain valid information and data needed to answer the problems in this study. The results of this study show that since the amendment to the Marriage Law, applications for Marriage Dispensation have increased, which are dominated by prospective brides. The reasons for filing Dispensation for Marriage by litigants from 2017 to 2022 are pregnancy and a very close relationship between the two prospective brides, where this is also in line with the considerations in the decisions of the Mamuju Religious Court Judges who granted many requests for Dispensation of Marriage.